The Covid-19 pandemic and regional economic resilience in northern Finland, Norway, and Sweden – a pre-study - Simonen, Jaakko; Moilanen, Mikko; Westin, Lars; Hersinger, Anders; Østbye, Stein; Svento, Rauli; Riepponen, Tapio (Luleå tekniska universitet, Industriell ekonomi, 2021)
The COVID-19 pandemic has been first and foremost a health crisis, but it has had severe negative impacts on northern economies. This pre-study report aims to provide a statistical review of the regional economic impacts as well as the recovery processes of the COVID-19 pandemic in the Arctic 5 cities in Northern Finland, Sweden, and Norway, i.e., Oulu and Rovaniemi in Finland, Luleå and Umeå in Sweden and Tromsø in Norway. Our cross-country regional research design makes it possible to study how the COVID-19 shock and the differences in national and regional containment regulations have affected these areas compared to the development in other regions and at the national level. This pre-study report will focus on the labour market effects of the pandemic and the role of sectoral structures in the Arctic 5 cities. The aim of our long-term research, which is based on this pre-study, is to analyse the short- and long-run regional economic impacts as well as the recovery processes of the COVID-19 pandemic in Northern Finland, Sweden, and Norway. Our goal is to provide valuable information about successful and less successful practices in these regions and thereby provide policy recommendations for the future. Regional effects will be analysed from the point of view of regional resilience.